Mental health during and after the COVID-19 pandemic – a longitudinal study over 42 months in five European countries - Zrnić Novaković, Irina; Ajduković, Dean; Ajduković, Marina; Kenntemich, Laura; Lotzin, Annett; Schäfer, Ingo; Anastassiou-Hadjicharalambous, Xenia; Evgeniou, Eleftheria; Borges, Camila; Figueiredo-Braga, Margarida; Russo, Moritz; Lueger-Schuster, Brigitte (European journal of psychotraumatology, 2025)
The mental health impact of the COVID-19 pandemic is well documented. However, only a few studies investigated mental health in later phases of the pandemic and after its official end. Moreover, little is known about people's psychological burden related to the pandemic and other global crises post-pandemic. Study's first objective was to compare mental health outcomes in the general population over the course of the pandemic and ten months post-pandemic. The second objective was to explore people's psychological burden regarding the pandemic, in comparison to current wars, climate crises, inflation, and poor government management and/or corruption in the post-pandemic era. Participants from the general population of Austria, Croatia, Germany, Greece, and Portugal (68.8% female, = 41.55) were assessed online up to four times between June 2020 and March 2024 (baseline sample: = 7913). (ADNM-8), (PHQ-2), and (WHO-5) were used to measure adjustment disorder, depression, and well-being. Prevalence rates were calculated and repeated measures ANOVAs applied to assess mental health at four time points. One-way repeated measures ANOVA was run to explore how the different global crises were related to participants' burden. Temporal variations in mental health were evident across four assessment waves, with highest levels of probable adjustment disorder and depression in winter 2020/2021 (T2). A slight improvement of mental health was found at later time points. Current wars and inflation were the greatest sources of psychological burden at the post-pandemic assessment, revealing some cross-country differences. Although mental health differences in the general population were not as pronounced as in the acute phase of the pandemic, psychosocial support is still needed post-pandemic. This is likely to be due to other global crises that take a toll on people's mental health.